Cost and returns of henna in Pali district of Rajasthan (Indian Journal of Arid Horticulture, 2025)
The present investigation was carried out in Sojat tehsil of Pali district in Rajasthan to study the cost of cultivation .A sample of 50 henna cultivators were selected for detailed study. The study relates to the agriculture year 2003-2004. Study of cost of cultivation revealed that the average total coast of cultivation of henna was estimated at Rs. 29978.00 ha'' with Rs. 21922.00 ha-1 as establishment cost and Rs. 8055.00 ha' as maintenance cost. In establishment cost henna seedlings and transplanting were the single largest cost items of operational cost in all the size groups of farms. Under maintenance cost, cost of rental value of owned land was the prime component of the fixed cost. The per hectare return over maintenance cost from henna cultivation on an average was estimated at Rs. 6155.00 for the life span of one year. The average net return over total cost of henna cultivation was worked out to be negative (Rs.15808.00 ha). The overall cost of production of henna was Rs. 28.71 kg'.
Keywords: Henna; production; economics